Effect of tumor compaction on the penetration of immune cells - Perisé-Badía, Ismael; Bayona, Clara; Randelovic, Teodora; Ochoa, Ignacio (Jornada de Jóvenes Investigadores del I3A, 2023)
The main goal of this project is to better better the obstacles that immune cells encounter when fighting glioblastoma tumors. An example is the high degree of compaction of these tumors, which makes it difficult for cells and drugs to penetrate. This phenomenon can be reversed with certain compounds, such as blebbistatin.